2018
DOI: 10.1590/1980-5373-mr-2017-0938
|View full text |Cite
|
Sign up to set email alerts
|

Lubricated Conditions Imposed on Coating Multi-layer on Wear Resistance Under Cr2O3 Effect

Abstract: Lubricated pin-on-disk sliding wear tests were performed on applied to Al-0.1Mg-0.35Ni-Si Alloy by using the spray coating method has been investigated. Different loads were 5, 10, and 15 N at a sliding velocity, 1.32 m/s at room temperature and 60% relative humidity. The surfaces were analyzed by using X-ray diffraction the residual (XRD), energy dispersive (EDS), scanning of (SEM) and (AFM), respectively. The results have showed that the thickness of Cr 2 O 3 coating was significantly related under the ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Lee Van performed erosion studies on types of ZTA covered iron matrix compounds and observed a 30-volt compound. Percent of ZTA particles confirmed the great resistance during put on test [18]. Friction and put on analyzes have been carried out on the Fe-Ni alloy matrix (Fe70Ni30).…”
Section: Introductionmentioning
confidence: 85%
“…Lee Van performed erosion studies on types of ZTA covered iron matrix compounds and observed a 30-volt compound. Percent of ZTA particles confirmed the great resistance during put on test [18]. Friction and put on analyzes have been carried out on the Fe-Ni alloy matrix (Fe70Ni30).…”
Section: Introductionmentioning
confidence: 85%
“…The high surface roughness will cause a reduction of the actual contact area between the counterpart and coating, which leads to a high load concentrated in a small area and ultimately enhances the coefficient of friction. 41 The lowest COF value of 0.107 AE 0.009 took place on Cr/CrN/CrAlSiN specimen during the friction test. Not only because the surface roughness of Cr/CrN/CrAlSiN sample was lowest, but also because the tribochemical products were formed on the contact interface.…”
Section: Corrosion Protection Performance Of As-preparedmentioning
confidence: 90%